CALCULATIONS OF WATER-CHEMICAL MODES FOR CIRCULATING COOLING SYSTEMS WITH THE WATER COOLING TOWERS - Кишневский, Е. В.; Кишневский, В. А.; Чиченин, В. В. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2011)
Prognostication method of circulating cooling systems with the cooling towers salt composition is expounded. Presence of error (7% and more), when using existent calculation and prognostication methods, is shown.